Factors Influencing Interest in Muslim Entrepreneurs as Financing Partners for Sharia P2P Lending - Chrisananda, Riska Anin; Sjam, Dewi; Rusgianto, Sulistya (Universitas Alma Ata, 2023)
This study aims to determine the factors that influence the interest of Muslim entrepreneurs in Sharia P2P lending. The determinant factor used is perceived ease of use, the subjective norm in Muslim circles, perceived usefulness, knowledge about riba, and review from the experience of financing partners. This study used a quantitative method tested by structural equation model (SEM) analysis techniques. Data were processed using SmartPLS 3.0 software. Data was obtained through an online questionnaire. Respondents who were used by UMKM, UKM, or startup business actor, Muslim, and had attended online classes and seminars on Sharia fintech. The number of respondents used was 90. The results show there were three predictors, perceived ease of use, the subjective norm in Muslim circles, and perceived usefulness that did not have a significant effect on behavioral intention, but two predictors of knowledge about riba and review from the experience of financing partners have a significant influence on behavioral intention